The moderating role of personal innovativeness and users experience in accepting the smart meter technology - Alkawsi G.; Ali N.; Baashar Y. (MDPI AG, 2023)
The rapid development of smart technologies and data analytics empowers most indus-tries to evolve their systems and introduce innovative applications. Consequently, smart metering technology, an internet of things-based application service, is diffusing rapidly in the energy sector. Regardless of its associated benefits, smart meters continue to struggle from consumers acceptance. To promote smart meters successful deployment, research is needed to better understand consumers acceptance of smart metering. Motivated by these concerns, a smart meter acceptance model is developed to evaluate the moderation role of experience and personal innovativeness factors among residential consumers. A cross-sectional research design was used in this study. Data were collected using a self-administrated questionnaire from 318 smart meters consumers who have had experience in using it. Hypothetical relationships were assessed and validated using partial least squares structural equation modelling. The empirical findings exert the moderating role of experience and personal innovativeness of smart meter acceptance that achieved an acceptable fit with the data, and specifically, five out of nine hypotheses were supported. 2021 by the authors. Licensee MDPI, Basel, Switzerland.